Юридичне поняття воєнної парадигми податкового права України - Дутчак, Остап (My University, 2024)
The article analyzes the legal concept of the military paradigm of tax law of Ukraine from the cognitive standpoint of anthroposociocultural and systemic approaches. As a result of the study of the issue, the author comes to the following conclusions: 1. One of the fundamentally important steps of the Ukrainian State, which has strategically important political and legal implications for Ukraine, especially for the entire further course of the Russian-Ukrainian war, is the introduction by it at the beginning of this war of the so-called military paradigm of tax law. This is one of the most unexpected, and therefore untested, social innovations. The military paradigm of tax law in Ukraine has become an essentially new phenomenon not only in the industry, but also in society. Nevertheless, it is of particular interest to the science of tax law. In order to understand all its conceptual novelty, its meaning and significance for the Ukrainian state, it is necessary, first of all, to clarify the legal concept of this paradigm. The most concise legal concept of the martial law paradigm of Ukraine's tax law should be understood as the doctrinal model of its tax law system during the period of martial law. The meaning of this concept is rooted in a special legal construction of tax. This construction is endowed with its inherent features: the purpose of this system; spontaneous dialogic nature, which is most fully manifested in its properties of reasonableness and fairness, adaptability and plasticity. A condition for its existence is a special external environment and the same fiscal risks. In practical terms, the military paradigm of Ukrainian tax law should be understood as a legitimately determined by the state method of fulfillment by the taxpayer of his fiscal obligation to the state, which is a logical consequence of the presence of purely attributable components. These components include: 1) the legal structure of the tax, which depends on the state; 2) the object of taxation, which depends on the taxpayer; 3) the functional ability of the taxpayer to fulfill its tax obligation to the state under martial law, which is independent of the above-mentioned subjects of the tax legal relationship to pay the tax. It is this third component which makes the martial law paradigm of tax law fundamentally different from its civilian (non-martial) paradigm.